Copy Number Variation of TLR-7 Gene and its Association with the Development of Systemic Lupus Erythematosus in Female Patients from Yucatan Mexico. (January 2014) - Pacheco, Guillermo Valencia; Cruz, Darig Cámara; Herrera, Lizbeth J. González; Mendoza, Gerardo J. Pérez; Amaro, Guadalupe I. Adrián; Ueji, Yumi E. Nakazawa; Ramírez, Angélica V. Angulo
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease characterized by the production of autoantibodies against self-antigens, which occurs most often in women between 15 and 40 years of age. The innate immunity is involved in the pathogenesis of SLE through TLR-7. Genetic factors such as copy number variation (CNV) of target genes may contribute to disease development, but this possible risk has not yet been studied in SLE patients from Yucatan, Mexico. The CNV of TLR-7 gene was determined by quantitative polymerase chain reaction assay using TaqMan probes in 80 SLE women and 150 control subjects. The results showed that 10% of SLE patients exhibited more than two copies of TLR-7 gene, whereas no mRNA overexpression was detected. These data suggested that increased CNV of the TLR-7 gene in Yucatan SLE women can be a risk factor for this disease.